1983
DOI: 10.1271/bbb1961.47.2133
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a novel metabolite from deoxynivalenol, a trichothecene mycotoxin, in animals.

Abstract: Deoxynivalenol(DON), 3a,7a,15-trihydroxy-12,13-epoxytrichothec-9-en-8-one, is a toxic metabolite such Fusarium spp. as F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 1 publication
2
53
0
Order By: Relevance
“…DOM-1 was first identified in urine from Wistar rats by Yoshizawa et al [24], further studies confirmed the presence of this metabolite in excreta of oral administered PVG rats [7,11]. On the other hand, DOM-1 was not detected in urine from Sprague-Dawley rats, that were found to contain a significant portion of DON glucuronide [9].…”
Section: Discussionmentioning
confidence: 92%
“…DOM-1 was first identified in urine from Wistar rats by Yoshizawa et al [24], further studies confirmed the presence of this metabolite in excreta of oral administered PVG rats [7,11]. On the other hand, DOM-1 was not detected in urine from Sprague-Dawley rats, that were found to contain a significant portion of DON glucuronide [9].…”
Section: Discussionmentioning
confidence: 92%
“…Detoxification of trichothecenes in vitro in bovine ruminal fluid by reductive deepoxidation, leading to 12,13-olefin, was first observed for DON (King et al, 1984). The same metabolite was found in urine and faeces of rats (Yoshizawa et al, 1983;Lake et al, 1987) and dairy cows (Cote et al, 1986) fed with DON. However, these experiments were performed by feeding whole animals with DON and it was not clear whether the transformation resulted from animal metabolism or from activities of microflora in their digestive tract.…”
Section: Detoxification Of Mycotoxins By Symbiotic Microflora Of Animmentioning
confidence: 92%
“…<5-10 ppm) represents any type of potential human health problem. However, the possibility of DON metabolite formation (Yoshizawa et al, 1983) should be investigated.…”
Section: Illustrated Inmentioning
confidence: 99%